Abortion-related near-miss morbidity and mortality in 43 health facilities with differences in readiness to provide abortion care in Uganda - Claudia Hanson; Josaphat Byamugisha; Susan Atuhairwe; Frank Kaharuza; Nazarius Mbona Tumwesigye (BMJ Global Health)
Introduction With a view to inform policy for improved postabortion care, we describe abortion-related near-miss and mortality by sociodemographic risk factors and management options by pregnancy trimester in Uganda.Methods This secondary data analysis used an adapted WHO near-miss methodology to collect cross-sectional maternal near-miss and abortion complications data at 43 health facilities in Central and Eastern Uganda in 2016–2017. We computed abortion severe morbidity, near-miss and mortality ratios per 100 000 live births, and described the proportion of cases that worsened to an abortion near-miss or death, stratified by geographical region and trimester. We tested for association between independent variables and abortion near-miss, and obtained prevalence ratios for association between second trimester near-miss and independent demographic and management indicators. We assessed health facility readiness for postabortion care provision in Central and Eastern regions.Results Of 3315 recorded severe abortion morbidity cases, 1507 were near-misses. Severe abortion morbidity, near-miss and mortality ratios were 2063, 938 and 23 per 100 000 live births, respectively. Abortion-related mortality ratios were 11 and 57 per 100 000 in Central and Eastern regions, respectively. Abortion near-miss cases were significantly associated with referral (p<0.001). Second trimester had greater abortion mortality than first trimester. Eastern region had greater abortion-related morbidity and mortality than Central region with facilities in the former characterised by inferior readiness to provide postabortion care.Conclusions Uganda has a major abortion near-miss morbidity and mortality; with mortality higher in the second trimester. Life-saving commodities are lacking especially in Eastern region compromising facility readiness for postabortion care provision.